Thomasine Traditions in Antiquity : The Social and Cultural World of the Gospel of Thomas - Asgeirsson, Jon Ma.; DeConick, April; Uro, Risto (Nag Hammadi and Manichaean Studies, 2006)
This volume is a selection of papers presented to the Society of Biblical Literature Thomasine Traditions Group from 1996 to 2001. The papers focus on the early Christian writings attributed to the apostle Thomas with particular emphasis on the Gospel of Thomas . The collection offers an extensive discussion of the social and cultural world of the gospel, particularly examining its relationship to other contemporary Christian writings and Graeco-Roman literature. The essays give a helpful survey of recent developments and discussions in the field of Thomasine studies. Among many topics dealt with in the volume are the issue of Thomas' "community," the gospel's enigmatic exhortation to become "passers-by," and Thomas' relation to the Hebrew epic, Platonic philosophic traditions, Valentinus, as well as to early gospel harmonies. The volume also proposes a hypothesis of the earliest layer of the Thomasine traditions and presents analyses of Thomas' argumentative rhetology and portrait of Jesus. One essay focuses on the role of the apostle Thomas in the Acts of Thomas . Thomasine Traditions in Antiquity will be a valuable tool for all those interested in Nag Hammadi Studies, Gnosticism, Early Christianity and the history of religion.